UPU portal to be opened for applications on Feb 24 - Siti Nur Azwin, Zulkapri (The New Straits Times Press (M) Bhd., 2020)
Applications to enrol in public higher-learning institutions for the 2020/2021 academic session will be opened starting from noon on Feb 24 through the Central University Admission Unit online portal (UPU online) at https://upu.moe.gov.my.